Identification of clinical factors predicting warfarin sensitivity after cardiac surgery. (August 2018) - Tyson, Karen; Hutchinson, Nevil; Williams, Sian; Scutt, Greg
Background: Warfarin is commonly initiated post-cardiac surgery to reduce the risk of intracardiac thrombus formation. Studies have found that sensitivity is increased after cardiac surgery and anticoagulation is subsequently difficult to manage. This study set out to identify clinical markers of increased warfarin sensitivity in patients after cardiac surgery, and build a model that can predict warfarin sensitivity, and improve safety in this setting. Methods: The study was an observational, retrospective cohort design. Clinical parameters including left ventricular ejection fraction (LVEF), cross-clamp time, age, serum albumin and C-reactive protein concentrations were collected from consenting patients who had undergone cardiac surgery and were prescribed postoperative warfarin. The warfarin dose index (WDI) was calculated for each patient from their international normalized ratio (INR) and warfarin dose, as a measure of sensitivity. Results: A total of 41 patients were recruited to the study. Logarithmically transformed WDI (log WDI) significantly correlated with LVEF, cardiopulmonary bypass (CPB) time, cross-clamp time, baseline INR and co-administration of amiodarone ( p < 0.05). When added to a linear regression model, LVEF and cross-clamp time produced a model that accounted for 41% of the variance in log WDI (R 2 = 0.41), p = 0.0002). Applying a log WDI cutoff value of −0.349 discriminated between patients who develop an INR > 4 and those who do not, with a sensitivity of 75% and a specificity of 70%. Conclusions: This single-centre study has highlighted two risk factors for increased warfarin sensitivity post-cardiac surgery. Further research is needed to confirm these findings in a wider, more diverse population, and to validate this model.